Exploration and prospect of the key technologies of the new generation mobile communication of intelligent railway - Yulong LU; Haiyan SHEN; Junyao ZHANG; Xinglei YANG; Yalong XIE; Lingling YANG (Dianxin kexue)
The progress of mobile communication technology drives industrial changes in all walks of life.The carrying capacity of the existing railway mobile communication system is increasingly difficult to meet the rapid growth of modern railway networks even after decades of development.Based on the requirements of intelligent railway applications for mobile communication bandwidth, delay, coverage and other challenges faced by the new generation of mobile communication, the critical technologies of new-generation mobile communication were focused on, such as the new generation of communication spectrum technology, channel coding technology, and multi-functional integrated radio frequency technology.Additionally, an “air-space-vehicle-ground integration” network aiming at seamless collaborative interaction of information among “vehicle-ground, vehicle-vehicle, and vehicle-person” was constructed.Furthermore, the application of communication-navigation integration, and communication-computing- storage integration were studied and prospected in intelligent railways.It will play a vital role in improving the service capability and efficiency of railway mobile communication and enable the development of China’s railway intelligence.